WHAT IF THE HUMAN MIND EVOLVED FOR NONRATIONAL THOUGHT? AN ANTHROPOLOGICAL PERSPECTIVE: with Pat Bennett and John A. Teske, "The Road Is Made by Walking: An Introduction"; J. Wentzel van Huyssteen, "Can We Still Talk about 'Truth' and 'Progress' in Interdisciplinary Thinking Today?"; Jonathan Marks, "What If the Human Mind Evolved for Nonrational Thought? An Anthropological Perspective"; Phillip Cary, "Right‐Wing Postmodernism and the Rationality of Traditions"; Margaret Boone Rappaport and Christopher Corbally, "Human Phenotypic Morality and the Biological Basis for Knowing Good"; Christian Early, "Philosophical Anthropology, Ethics, and Love: Toward a New Religion and Science Dialogue"; Warren S. Brown, "Knowing Ourselves as Embodied, Embedded, and Relationally Extended"; and John A. Teske, "Knowing Ourselves by Telling Stories to Ourselves.". Issue 3 (18th August 2017) - Marks, Jonathan
Abstract: Our knowledge of the evolution of human thought is limited not only by the nature of the evidence, but also by the values we bring to the authoritative scientific study of our ancestors. The tendency to see human thought as linear progress in rational (i.e., problem‐solving) capacities has been popular since the Enlightenment, and in the wake of Darwinism has been extended to other species as well. Human communication (language) can be used to transmit useful information, but is rooted in symbolic processes that are nonrational—that is, they involve choosing among functionally equivalent alternatives, any of which is as good an option as any other. The evolution of human thought cannot be realistically isolated from the evolution of human society or human communication, neither of which is rooted in obvious rationality.